Abdominal multi-organ iron content and the risk of Parkinson’s disease: a Mendelian randomization study - Yang, Mingrui; Tang, Cheng; Peng, Fei; Luo, Chaotian; Chen, Guowei; Kong, Rong; Peng, Peng (Frontiers in Aging Neuroscience, 2024)
Background To evaluate the causal relationship between abdominal multi-organ iron content and PD risk using publicly available genome-wide association study (GWAS) data. Methods We conducted MR analysis to assess the effects of iron content in various abdominal organs on PD risk, followed by reverse analysis. Additionally, MVMR analysis evaluated the independent effects of organ-specific iron content on PD. We utilized genetic variation data from the UK Biobank, including liver iron content (n = 32,858), spleen iron content (n = 35,324), and pancreas iron content (n = 25,617), as well as summary-level data for Parkinson’s disease from the FinnGen (n = 218,473) and two other large GWAS datasets of European populations (First dataset n = 480,018; Second dataset n = 2,829). The primary MR analysis used the inverse variance-weighted (IVW) method, confirmed by MR-Egger and weighted median methods. Sensitivity analysis was performed to address potential pleiotropy and heterogeneity. Observational cohort results were validated through replication cohort analysis, followed by meta-analysis. Results IVW analysis revealed a causal relationship between increased liver iron content and elevated risk of PD (OR = 1.27; 95% CI: 1.05–1.53; p = 0.015). No significant causal relationship was observed between spleen (OR = 1.00; 95% CI: 0.76–1.32; p = 0.983) and pancreatic (OR = 0.93; 95% CI: 0.72–1.20; p = 0.573) iron content and increased risk of PD. Meta-analysis of GWAS data for PD from three different sources using the random-effects IVW method showed a statistically significant causal relationship between liver iron content and the occurrence of PD (OR = 1.17, 95% CI: 1.01–1.35; p = 0.012). Conclusion This study presents evidence from Mendelian randomization (MR) analysis indicating a significant causal link between increased liver iron content and a higher risk of Parkinson’s disease (PD). These findings suggest that interventions targeting body iron metabolism, particularly liver iron levels, may be effective in preventing PD.